1988
DOI: 10.1111/j.1365-3024.1988.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to the human hookworm Necator americanus in mice

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…There were no significant differences between the weights of control and infected groups in Exp. 3. been shown to occur in the case of N. americanus in mice (Wells & Behnke, 1988). Despite finding an occasional larva in the musculature we concluded that significant tissue migration was unlikely to have occurred following oral exposure to the parasite.…”
Section: Discussionmentioning
confidence: 67%
“…There were no significant differences between the weights of control and infected groups in Exp. 3. been shown to occur in the case of N. americanus in mice (Wells & Behnke, 1988). Despite finding an occasional larva in the musculature we concluded that significant tissue migration was unlikely to have occurred following oral exposure to the parasite.…”
Section: Discussionmentioning
confidence: 67%
“…There is no robust experimental animal model that parallels the course of hookworm infection in humans. Human hookworm species do not mature in mice . Hamsters are (at best) a semi‐permissive host to these species and, although they can be infected with N. americanus , the infection time is much shorter and the worm burden much lower than in humans .…”
Section: Introductionmentioning
confidence: 99%
“…Despite H. polygyrus bakeri does not infect through the skin or migrate through the lungs (as it depends on oral ingestion of infective larvae), it has been extensively employed as a model for human hookworm infections. Indeed, similarly to hookworms, H. polygyrus bakeri induces chronic intestinal infections in several mice strains, and the modified Th2 cell responses induced by infection (a Th2-like response linked with the production of anti-inflammatory cytokines and Treg activity) does not completely eliminate the parasites (Wells and Behnke, 1988;Maizels, 2005;Bungiro et al, 2008;Reynolds et al, 2012;Nair and Herbert, 2016). Furthermore, the study of H. polygyrus bakeri and N. brasiliensis infection in rodents has provided the immunology community with important information about the humoral and cellular mechanisms involved in the induction and development of Th2 immune responses and their capacity in protecting against helminth infections (Ogilvie and Jones, 1971;Ishizaka et al, 1976;Urban et al, 1991;Camberis et al, 2003).…”
Section: Introductionmentioning
confidence: 99%